Elevage de la dorade coryphène (Corypheana hippurus) - Ayari A.; Ben Ouada H.; Peyrou B. (Marine aquaculture finfish species diversification, 1995)
Spawning, larvae rearing, weaning and first ongrowing of Corypheana hippurus are experimented at the AST hatchery in Tunisia. 67 juveniles are collected from the sea and acclimatised to be used as a brood stock. Sexual maturity begins since 1.5 kg body mean weight. Spawns are obtained daily when temperature is maintained at 23 degrees C. The pelagic eggs size varies between 1600 and 1800 microns. Fecundity and hatch rates are respectively 90 and 85 per cent. Incubation lasts 40 hours at 22 degrees C which is the optimal temperature. Larvae rearing during 20 days is conducted on these conditions: temperature 22 degrees C, density 50 larvae/l and feeding by Artemia nauplii. The survival rate is only 1 per cent, the highest mortality is seen between 11th and 12 day age old. Weaning and first ongrowing shows high growth performance (about 100 gr. after 4 months), nevertheless survival rate is still very low (4 per cent) caused principally by cannibalism which begins, early since 20th day age old, and continues throughout this rearing period.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)